2011
DOI: 10.1016/j.jeem.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Does marginal price matter? A regression discontinuity approach to estimating water demand

Abstract: Although complex pricing schedules are increasingly common in utility billing, it is difficult to determine whether consumers respond to complicated marginal prices because price changes are often confounded with simultaneous demand shocks or non-price policies. To overcome this challenge, we exploit a natural experiment -the introduction of a third price block in an increasing block pricing schedule for water -in Santa Cruz, California. Using a regression discontinuity design, we find that consumers do respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 15 publications
2
64
1
Order By: Relevance
“…Borenstein (2009) also finds evidence that electricity consumers are responding either to average price or expected marginal price (which entails averaging over uncertain consumption) rather than the actual marginal price paid. Nataraj and Hanemann (2011) conclude that water consumers do respond to changes in marginal price. The extent to which these discrepancies are due to fundamental differences between water and electricity consumption, and/or between the price structures under investigation, is a topic for future work.…”
mentioning
confidence: 90%
“…Borenstein (2009) also finds evidence that electricity consumers are responding either to average price or expected marginal price (which entails averaging over uncertain consumption) rather than the actual marginal price paid. Nataraj and Hanemann (2011) conclude that water consumers do respond to changes in marginal price. The extent to which these discrepancies are due to fundamental differences between water and electricity consumption, and/or between the price structures under investigation, is a topic for future work.…”
mentioning
confidence: 90%
“…No attempt was however made to quantify the economic impact a change in a block water tariff has on price elasticity. Nataraj and Hanemann (2011) analysed the impact of the introduction of a third price block on residential water consumption in Santa Cruz, and concluded that consumers who expected to face the higher marginal price in the 3 rd block would reduce their consumption.…”
Section: Introductionmentioning
confidence: 99%
“…forecast its demand, to analyze and interpret the human interactions and to adjust the pricing policy (Emelko et al, 2011;Nataraj and Hanemann, 2011). Additionally, some authors have also included other variables such as temperature, rainfall, geographical factors, and sun-light period (Abdel-Aal and Al-Garni, 1997; Blaney and Inglis, 1980;Paatero and Lund, 2006;Stokes et al, 2004).…”
Section: Implementation Of Pricing Policies For Peak Water Demand Permentioning
confidence: 99%
“…These changes and others are key factors that exacerbate the imbalance between the demand and availability of fresh water resources, with a growing recognition that the current situation is unsustainable (Almeida et al, 2013;Arbués et al, 2003;Nataraj and Hanemann, 2011).…”
Section: Introductionmentioning
confidence: 99%